2018
DOI: 10.1186/s12934-018-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Engineering de novo anthocyanin production in Saccharomyces cerevisiae

Abstract: BackgroundAnthocyanins are polyphenolic pigments which provide pink to blue colours in fruits and flowers. There is an increasing demand for anthocyanins, as food colorants and as health-promoting substances. Plant production of anthocyanins is often seasonal and cannot always meet demand due to low productivity and the complexity of the plant extracts. Therefore, a system of on-demand supply is useful. While a number of other (simpler) plant polyphenols have been successfully produced in the yeast Saccharomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 61 publications
4
50
0
Order By: Relevance
“…Moreover, compared with the 24-h and 48-h time points, gene expression levels in strain S22-H were increased at 72 h post-inoculation. This suggested that at 72 h post-inoculation, the synthesis of heterologous proteins required the participation of protein folding and assembly genes, which was consistent with the results of xylanase gene and enzyme production analyses for this strain 4…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, compared with the 24-h and 48-h time points, gene expression levels in strain S22-H were increased at 72 h post-inoculation. This suggested that at 72 h post-inoculation, the synthesis of heterologous proteins required the participation of protein folding and assembly genes, which was consistent with the results of xylanase gene and enzyme production analyses for this strain 4…”
supporting
confidence: 86%
“…Approved by the Food and Drug Administration of the United States as a safe species, Saccharomyces cerevisiae is an ideal host for the expression of enzymes used in food and feed production [4] . With its clear biological and genetic background, S. cerevisiae boasts the advantageous features of prokaryotes, including fast growth and reproduction and simple genetic manipulation procedures, as well as post-translational modification of heterologous proteins that is common to eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the production levels in the 5-L bioreactor reached 1.7 g/L. Use of S. cerevisiae in synthesis of glycosylated natural products has been reported widely [16,28,29]. The findings from this study may be used to synthesize other glycosylated natural products using S. cerevisiae, and the cost of production can be reduced by using glycerin to synthesize natural products.…”
Section: Resultsmentioning
confidence: 64%
“…The flavonoid pathway has been diversified in E. coli and yeast to yield the dihydrochalcone phloretin and its derivatives, the flavanone liquiritigenin, and the flavonols kaempferol, quercetin, and fisetin, among others (Table 1). This pathway was extended to produce anthocyanin pigments using E. coli polycultures (Jones et al, 2017) and a single engineered yeast strain (Eichenberger et al, 2018;Levisson et al, 2018).…”
Section: Pioneering Studies In the Microbial Synthesis Of Plant Metabmentioning
confidence: 99%
“…The same pathway has been reconstructed within a single S. cerevisiae strain (Galanie et al, 2015), albeit at lower titers, again highlighting the potential advantages of eukaryotic hosts for synthesizing complex plant secondary metabolites. Analogously, de novo anthocyanin synthesis in E. coli employed four engineered strains (Jones et al, 2017), which again contrasts strategies using S. cerevisiae in which a single strain hosts the full anthocyanin pathway (Eichenberger et al, 2018;Levisson et al, 2018). Although yeast is clearly favored for harboring downstream pathways, precursor titers are often higher in E. coli (e.g., for production of tyrosine, p-coumaric acid, dopamine, reticuline, and taxadiene; Table 1).…”
Section: Workhorses and Specialized Hostsmentioning
confidence: 99%